A drug-loaded composite coating to improve osteogenic and antibacterial properties of Zn–1Mg porous scaffolds as biodegradable bone implants - Zhenbao Zhang; Aobo Liu; Jiadong Fan; Menglin Wang; Jiabao Dai; Xiang Jin; Huanze Deng; Xuan Wang; Yijie Liang; Haixia Li; Yantao Zhao; Peng Wen; et al. (Bioactive Materials, 2023)
Zinc (Zn) alloy porous scaffolds produced by additive manufacturing own customizable structures and biodegradable functions, having a great application potential for repairing bone defect. In this work, a hydroxyapatite (HA)/polydopamine (PDA) composite coating was constructed on the surface of Zn–1Mg porous scaffolds fabricated by laser powder bed fusion, and was loaded with a bioactive factor BMP2 and an antibacterial drug vancomycin. The microstructure, degradation behavior, biocompatibility, antibacterial performance and osteogenic activities were systematically investigated. Compared with as-built Zn–1Mg scaffolds, the rapid increase of Zn2+, which resulted to the deteriorated cell viability and osteogenic differentiation, was inhibited due to the physical barrier of the composite coating. In vitro cellular and bacterial assay indicated that the loaded BMP2 and vancomycin considerably enhanced the cytocompatibility and antibacterial performance. Significantly improved osteogenic and antibacterial functions were also observed according to in vivo implantation in the lateral femoral condyle of rats. The design, influence and mechanism of the composite coating were discussed accordingly. It was concluded that the additively manufactured Zn–1Mg porous scaffolds together with the composite coating could modulate biodegradable performance and contribute to effective promotion of bone recovery and antibacterial function.